PERAN MOTIVASI BELANJA DAN KONTROL DIRI TERHADAP PERILAKU KONSUMTIF PADA K-POPER PEREMPUAN REMAJA AKHIR - Tarisha Azzahra Saneva; Ninawati Ninawati; Meike Kurniawati (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2022)
This research aimed to determine the effect of shopping motivation and self-control on consumptive behavior in K-poper late adolescent girls. K-Pop fans or also known as K-popers are a group of people who like / enjoy music that comes from South Korean singers. This study used a non-experimental quantitative method with 387 late adolescent girls as participants aged 18-21 years who buy Korean merchandise in North Sumatra. This study used a measuring instrument The Brief Self-control Scale, a measuring tool for consumptive behavior, and a measuring tool for shopping motivation. Data processing was using Statistical Product and Service Solutions (SPSS) version 25. The results of this study indicated that there is an effect of self-control on consumptive behavior with a percentage of 24% and the effect of shopping motivation on consumptive behavior with a percentage of 1%. The conclusion of this research showed that the role of self-control on consumptive behavior is much greater than shopping motivation.